SEEDS OF TRADITION: . - Sahi, jyothi (Journal of Dharma, 1998)
To express this coming together of communities, to share a common culture, we could use the term "global culture". The problem with the terminology suggested by the term "Little Traditions" as opposed to some Great Tradition, which is supposed to embrace a more widely distributed cultural identity, is that it is implied that this Great Tradition represents a cultural expression which is common to a greater number of people. Paradoxically, however, most human beings belong to some form of little tradition, and the so-called "Great Tradition" is very much restricted to a certain cultural elite. The fact is that all cultures are "little Traditions" of one sort or another, and difference, or variety, is much more characteristic of cultural forms, than similarity. Ofcourse, this does not deny the fact that there have been various attempts to create a synthesis of cultures, taking elements from different cultures, and creating a new type of culture which Attempts to combine what is perceived to be best, or most vital, in different cultural traditions.